Ketidakstabilan Nilai Tukar dan Dampaknya Terhadap Kinerja Keuangan Perusahaan - Yusuf, Nurhidaya; Baharuddin, Nabila; Idris, Ismayanti; Anisafitri (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2026)
Exchange rate instability can impact a company's financial performance, particularly for companies engaged in international trade. This study aims to analyze the effect of exchange rate fluctuations on the financial performance of companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024. This study uses a quantitative approach with descriptive and causal research methods, and analyzes secondary data using multiple linear regression. The results indicate that exchange rate fluctuations have a negative impact on financial performance, particularly for companies with high international exposure. Companies that manage exchange rate risk with hedging strategies are better able to maintain their financial performance. Therefore, companies are advised to pay attention to exchange rate risk management to maintain stability in the face of market uncertainty.